High mortality with High false negative rate: COVID-19 infection in patients with hematologic malignancies. (July 2021) - Niu, Alex; Ning, Bo; Socola, Francisco; Safah, Hana; Reynolds, Tim; Ibrahim, Moayed; Safa, Firas; Alfonso, Tina; Luk, Alfred; Mushatt, David M.; Hu, Tony; Saba, Nakhle S.
Highlights: Blood cancers are associated with high rates of SARS-CoV-2 RT-PCR false negativity. False negative RT-PCR COVID-19 results can be detected by CRISPR-based assays. COVID-19 in patients with hematologic malignancies confers worse survival. Lympho-depleting chemotherapy may result in higher COVID-19 mortality.